Numerical analysis of free vibration of cross-ply thick laminated composite cylindrical shells by continuous element method - Hien, Ta Thi; Thinh, Tran Ich; Cuong, Nguyen Manh (Vietnam Journal of Mechanics, 2013)
This paper presents the vibration analysis of thick laminated composite cylindrical shells by a new approach using the Continuous Element Method (CEM). Based on the analytical solutions for the differential equations of thick composite cylindrical shell taking into account shear deflection effects, the dynamic transfer matrix is built from which natural frequencies are easily calculated. A computer program is developed for performing numerical calculations and results from specific cases are presented. Numerical results of this work are compared with published analytical and Finite Element Method (FEM) results. Through different examples, advantages of CEM are confirmed: reduced size of model, higher precision, reduced time of computation and larger range of studied frequencies.